Victorian poetry now : poets, poems, poetics - Cunningham, Valentine (Chichester, West Sussex ; Malden, Mass. : Wiley-Blackwell, 2011)
"Poised on the brink of modernism and the twentieth century, the Victorian era was the most productive period of poetry there has ever been, in any language. This book is the definitive guide to the range of Victorian poets and poems, from the famous to the less well known. Approaching the poets and poems in the light of both Victorian and modern critical concerns, this absorbing book places poetry written during the nineteenth century in its personal, aesthetic, historical, and ideological contexts, and considers the poets' major anxieties, such as self, body, and melancholy. The author insists that rhyming and repetition are the major formal features of this (or any) poetry and focuses on the Victorian obsession with small subjects in small poems. The Victorians, at the helm of a global empire, were innovative and ambitious, and the poetry of the age reflects the aspirations and self-consciousness of Victorian society. Esteemed critic, Valentine Cunningham, exhibits encyclopedic knowledge of the poetry produced in this period and, with dazzling close readings of a number of poems, cuts through the often complex Victorian poetic form to reveal the key themes and contexts of the poems and the passions that drove the men and women who wrote them"--
pt. 1. So far as the words are concerned -- pt. 2. Contents and discontents of the forms.
Includes bibliographical references and index.
Print version record.
Keywords: 1800-1899; English poetry -- 19th century -- History and criticism; Poetics -- History -- 19th century; Poetry -- Authorship -- History -- 19th century; Literature and society -- Great Britain -- History -- 19th century; POETRY -- English, Irish, Scottish, Welsh; English poetry; Literature and society; Poetics; Poetry -- Authorship; Great Britain; Electronic books; Criticism, interpretation, etc; History